Localising the Global: The WHO International Health Regulations and Domestic Health Governance Mechanisms of Infectious Diseases in Nigeria (Journal of Governance and Development (JGD), 2016)
The importance of international health law, particularly the International Health Regulations (IHR 2005) adopted under the auspices of the World Health Organisation, has been widely acknowledged by scholars and policy makers. Given its importance in global governance of infectious diseases and global health security, aspects of the IHR feature prominently in the literature on global health governance, law and diplomacy. Apparently, case studies dealing with its impact on specific countries remain under researched. Against this background, this article examines the impact of IHR 2005 on domestic health governance mechanisms of infectious diseases in Nigeria. This article argues that Nigeria has made remarkable progress in terms of governance of infectious diseases manifested in legal responses, institutional arrangements and policy initiatives. It concludes that what is needed at this point is for Nigeria to improve on, and sustain these health governance mechanisms, which were instrumental in the successful containment of the Ebola Virus Disease outbreak in 2014.